A Trifacacking System for Dynamic Subset Targets using Probability Hypothesis Filtering. Issue 37 (2022) - Perera, R.A. Thivanka; Phillips, Andrew; Yuan, Chengzhi; Stegagno, Paolo
Abstract: In this paper we present a novel formulation of the multi-target tracking problem in which the target represents a variable shape and size subset of the state space. Due to the nonlinear nature of the system and the inherent multi-target nature of the problem, we provide a solution based on the particle implementation of the PHD filter. Testing in simulations yields promising results allowing a significant reduction of the errors with respect to measurements.